Industrial relations in Port Klang Authority: a case study / Fahitah Shamsuddin - Shamsuddin, Fahitah (Faculty of Law, 1982)
The object of writing this project paper on Industrial Relations is to examine some disputes on wages and promotion of employees in Port Klang Authority (PKA) after the implementation of the Harun Salaries Report in 1975. The disputes are examined in the context of the broader issues affecting wage negotiations and personnel policy of statutory bodies. The standardization of wages and conditions of service in statutory bodies in the 1980's has resulted in greater control and created problems of delay,conflict in decision-making among agencies, rigidity in wage settlement and direct confrontation between the Trade Union and the Government. Uniformity in personnel policy,emphasis on paper qualifications in the recruitment of employees and the lack of promotional prospects have failed to attract good staff. Retaining existing staff is also a major problem